The Paradigm of Science IntegrationiIn Islamic University:The Historicity and Development Pattern of Islamic Studies in Indonesia - Efrinaldi, Efrinaldi; Andiko, Toha; Taufiqurrahman, Taufiqurrahman (Madania: Jurnal Kajian Keislaman, 2020)
This article aims to discuss the patterns of science integration in Islamic universities in Indonesia and the development models. This study used qualitative method, the data source consists of informants and documentation, as well as data collection techniques carried out through in-depth interviews, participant observation, focus group discussions and documentation review. As results, the application of science integration patterns in several Islamic universities turns out to be different, based on different understanding of the concept of science integration and local socio-cultural settings, according to the their respective established backgrounds. The State Islamic University (UIN) generally applies integration, not Islamization, by combining Islamic science and general science. This is stated in the vision and mission of higher education. As for practice, the implementation of science integration is applied to the faculty through direct policy from the university. In general, Islamic universities in Indonesia have already had a philosophical paradigm, by carrying out a distinctive concept of science integration. In the elaboration aspect of the integration paradigm, it is reflected in the applied curriculum. However, from the explanation, science integration actually aims at integrating religious disciplines with modern technology and science, which is implemented in Islamic higher education in Indonesia. In developing the concept of science integration in each UIN in Indonesia, it has editorial diversity and contextual elaboration with the environment and culture of respective regions. Artikel ini bertujuan membahas pola integrasi keilmuan pada perguruan tinggi Islam di Indonesia dan model pengembangannya. Penelitian ini menggunakan metode kualitatif, sumber datanya terdiri dari informan dan dokumentasi, serta teknik pengumpulan datanya dilakukan melalui wawancara mendalam, observasi partisipasi, focus group discussion dan telaah dokumentasi. Hasilnya, penerapan pola integrasi keilmuan pada beberapa lembaga perguruan tinggi Islam tersebut ternyata berbeda-beda, berdasarkan perbedaan pemahaman tentang konsep integrasi keilmuan dan setting sosial-budaya yang bersifat lokal, sesuai latar belakang perguruan tinggi itu didirikan. Universitas Islam Negeri (UIN) umumnya menerapkan integrasi, bukan islamisasi, yaitu dengan memadukan antara Islamic science dan sains umum. Ini tertuang dalam visi dan misi perguruan tinggi. Adapun prakteknya, pelaksanaan integrasi keilmuan diterapkan pada fakultas melalui kebijakan langsung dari universitas. Secara umum, Perguruan Tinggi Islam di Indonesia telah memiliki paradigma filosofis, dengan mengusung konsep integrasi keilmuan yang khas. Dalam aspek penjabaran paradigma integrasi tersebut, tercermin dalam kurikulum yang diterapkan. Namun, dari penjabarannya integrasi keilmuan sesungguhnya ingin memadukan disiplin ilmu keagamaan dengan teknologi dan sains modern, yang diimplementasikan dalam pendidikan tinggi Islam di Indonesia. Dalam pengembangan konsep integrasi keilmuan di masing-masing UIN di Indonesia memiliki keragaman redaksional dan elaborasi yang sangat kontekstual dengan lingkungan dan kultur daerah masing-masing.